2023
DOI: 10.1002/ncp.10980
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the use of oral nutrition supplements on clinical outcomes among patients who have undergone surgery for hip fracture: A literature review

Abstract: Older adults who have undergone surgery for hip fracture are often malnourished or at risk for malnutrition, and providing oral nutrition supplements is a common intervention used to help meet nutrition needs postoperatively among this population. A literature search was conducted to examine the effects of oral nutrition supplementation on postoperative outcomes among patients ≥55 years old who had undergone surgery for hip fracture. Three randomized controlled trials that met inclusion criteria are examined i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 64 publications
0
2
0
Order By: Relevance
“…One nutritional intervention for malnourished patients is the use of high-protein, high-calorie oral nutritional supplements (ONS) [ 23 ]. The intake of essential amino acids is required for muscle synthesis and effectively improves muscle strength [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…One nutritional intervention for malnourished patients is the use of high-protein, high-calorie oral nutritional supplements (ONS) [ 23 ]. The intake of essential amino acids is required for muscle synthesis and effectively improves muscle strength [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…In patients with normal renal function, protein intake of 2 g/kg/d has been proposed to aid bone healing, maintain lean muscle mass, and reduce complications 75,81,82 . Incorporation of hydroxy-beta-methylbutyrate (HMB), a metabolic product of leucine, in oral nutritional supplementation has been shown to improve postoperative outcomes after hip fracture by preserving muscle mass and improving sarcopenia markers 77 .…”
Section: The Impact Of Malnutrition In Orthopaedic Surgerymentioning
confidence: 99%
“…Three randomized controlled trials have suggested that use of a high-protein, high-calorie oral nutrient supplement was associated with improvements in markers of sarcopenia and functional status 77-80 . In patients with normal renal function, protein intake of 2 g/kg/d has been proposed to aid bone healing, maintain lean muscle mass, and reduce complications 75,81,82 .…”
Section: The Impact Of Malnutrition In Orthopaedic Surgerymentioning
confidence: 99%